2010
DOI: 10.1061/(asce)gt.1943-5606.0000235
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strength of Fiber-Reinforced Sands

Abstract: Consolidated-drained triaxial compression tests were conducted to compare the stress-strain and volume change response of sands and clayey sands reinforced with discrete randomly distributed polypropylene fibers. The influence of various test parameters such as fiber content (0.0%, 0.5% and 1.0% by weight), clay content (0%, 10% and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(47 citation statements)
references
References 27 publications
9
38
0
Order By: Relevance
“…The results show that, in general, the increase in composite strength is in proportion with the fibre factor of the composite. This is in agreement with the soil testing results reported by many researchers such as Zorberg (2002 & 2013), Michalowski and Cermák (2002), Sadek et al (2010), Gray and Ohashi (1983), Gray and Maher (1989) and Diambra et al (2009).…”
Section: Fibre Reinforced Soil Displacements and Strainssupporting
confidence: 82%
See 1 more Smart Citation
“…The results show that, in general, the increase in composite strength is in proportion with the fibre factor of the composite. This is in agreement with the soil testing results reported by many researchers such as Zorberg (2002 & 2013), Michalowski and Cermák (2002), Sadek et al (2010), Gray and Ohashi (1983), Gray and Maher (1989) and Diambra et al (2009).…”
Section: Fibre Reinforced Soil Displacements and Strainssupporting
confidence: 82%
“…Figure 2.22 illustrates the model proposed by Gray and Ohashi (1983) investigators (Gray and Ohashi 1983;Gray and AI-Refeai 1986;Maher and Gray, 1990) The real shear behaviour of the FRS depends typically on the loading direction largely as a result of anisotropic fibre orientation. and coarse sand (Sadek, 2010) The failure envelope has two segments: a linear part associated with fibre pull out, and a nonlinear one related to yielding or breakage of the fibre material.…”
Section: ( )mentioning
confidence: 99%
“…Sadek et al [4] reported an experimental investigation for evaluating the shear strength of fiber reinforced sand. The addition of fibers with an aspect ratio ranging from 40 to 150 and fiber content ranging from 0.5 to 1.5 % was found to increase the shear strength and the ductility of sand-fiber composite.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various experimental means, direct shear tests have been widely employed to simulate the pullout failure of fibers/roots along a shear bandelike failure plane (Athanasopoulos 1996;Liu et al 2009;Sadek et al 2010). Meanwhile, being a proven way to explore soil behavior under a wide range of confining pressure, triaxial compression tests have been frequently used for the study of fiberreinforced soils (Gray and Al-Refeai 1986;Consoli et al 2007b).…”
Section: Introductionmentioning
confidence: 99%